Efficiency of Fornas Drug Procurement via E-Catalogue: Comparative Analysis of Price and Stock Availability Before and After Mandate - Wulandari, Siswi; Bram Mustiko Utomo (Journal of Health Service Administration and Hospital Management, 2025)
This study evaluates the efficiency of National Formulary (Fornas) drug procurement via Indonesia’s mandatory E-Catalogue system by comparing drug prices and stock availability before and after its adoption. Using a retrospective quantitative design and Dual-Weighted Analysis (incorporating linear regression), this study analyzed 60 essential Fornas drugs using official LKPP pricing data and aggregated healthcare stock reports. Results conclusively show a significant 18.13% price reduction and price standardization post-implementation (p < 0.001), demonstrating strong financial efficiency. However, logistical efficiency remains unproven; aggregate stock availability increased only marginally by 2.7% (p=0.053), with a notable decline observed for high-cost vital drugs (Stratum A). The Simple Linear Regression analysis further reveals no statistically significant correlation between the realized price reduction and improvements in stock reliability (R = -0.15, p = 0.254). Findings highlight that while the E-Catalogue effectively serves as a cost brake, it does not yet ensure reliable supply for critical medicines, pointing to a fundamental dissociation between financial and logistical efficiency. Policy recommendations include revising pricing mechanisms for vital drugs, enhancing logistical monitoring, and strengthening demand planning capabilities. This research provides critical insights for policymakers and contributes to the evaluation of public pharmaceutical procurement policy beyond sole cost metrics.